Towards ontology alignment of e-business standards using OWL and F-logic. (1st January 2011) - Schatten, Markus; Magdalenic, Ivan; Vrdoljak, Boris
In this paper a mapping of Core Components specification based e-business standards to an ontology is presented and a framework for ontology alignment based on F-logic is proposed. The well accepted Web Ontology Language (OWL) is used for ontology development. In order to preserve the existing hierarchy of the standards, an emphasis is put on the mapping of Core Components elements to specific constructs in OWL. The main purpose of developing an e-business standards' ontology is to create a foundation for an automated mapping system that would be able to convert concepts from various standards in an independent fashion. The practical applicability and verification of the presented mappings is tested on the mapping of Universal Business Language version 2.0 and Cross Industry Invoice version 2.0 to OWL. Additionally we propose a 4-rules class alignment technique which is formalised in F-logic – a deductive object-oriented rule-based language for ontology management.